The Burden of Disease in Alopecia Areata: Canadian Online Survey of Patients and Caregivers - Anthony Justin Gilding; Nhung Ho; Elena Pope; Cathryn Sibbald (JMIR Publications, 2022)
BackgroundAlopecia areata (AA) is associated with negative impacts on the quality of life (QoL). Data on this impact are lacking for Canadian patients and their caregivers. ObjectiveThis study aims to investigate the burden of AA on Canadian patients and their caregivers. MethodsWe created 4 online surveys for patients 5-11 years old, 12-17 years old, and ≥18 years old and for caregivers of children (<18 years old) with AA. These were disseminated through the Canadian Alopecia Areata Foundation (CANAAF) website and to dermatologists across Canada. ResultsIn total, 115 adult patients (n=100, 87%, female), 14 pediatric patients (n=13, 92.9%, female), and 15 caregivers completed the surveys online. The majority (n=123, 95%) of patients felt uncomfortable or self-conscious about their appearance. Camouflaging hair loss with hats, scarves, and hairpieces was a common practice for 11 (78.6%) pediatric and 84 (73%) adult patients. Avoidance of social situations was reported by 8 (57.1%) pediatric and 75 (65.2%) adult patients. Constant worry about losing the achieved hair growth was a concern for 8 (57.1%) pediatric and 75 (65.2%) adult patients. On a scale of 1-5, the mean score of caregivers' own feelings of sadness or depression about their child's AA was 4.0 (SD 0.9) and of their feelings of guilt or helplessness was 4.2 (SD 1.2). The impact on the QoL was moderate for both children and adults. Based on the Adjustment Disorder New Module-20 (ADNM-20), 71 (61.7%) of 115 patients were at high risk of an adjustment disorder. Abnormal anxiety scores were recorded in 40 (34.8%) patients compared to abnormal depression scores in 20 (17.4%) patients. ConclusionsThis study confirmed a significant burden of AA on Canadian patients' and caregivers' QoL.